SCHEMA EVOLUTION SUPPORT IN HYBRID TRANSACTIONAL/ANALYTICAL PROCESSING (HTAP) WORKLOADS - Diaconu, Christian; Zhu, Wumengjian; Luo, Chen; McElhanney, Corbin (2025)
The subject technology receives a request to perform a table scan operation of a table. The subject technology determines that the table is being accessed for an initial time. The subject technology populates a columnar cache with data of the table provided by the table scan operation. The subject technology determines a set of schema versions of a set of rows from the data of the table. The subject technology determines schema information of each schema from the set of schema versions. The subject technology generates a result rowset and a second rowset comprising a union of columns that have appeared at least once in each row. The subject technology performs deserialization of rows from the result rowset and the second rowset. The subject technology provides the rows from the result rowset and the second rowset to write to a file in a particular format.